2021
DOI: 10.46849/guiibd.931825
|View full text |Cite
|
Sign up to set email alerts
|

Ab Ülkeleri̇nde Kamudaki̇ Kurumsal Kali̇teni̇n Ekonomi̇k Büyümeye Etki̇si̇: Panel Veri̇ Anali̇zi̇

Abstract: There are many empirical studies in the literature about the relationship between institutional factors and economic performance. In some of these studies, one-way relationships were observed among the relevant variables, and bilateral relationships were observed at others. In this research, based on the available literature, the possible impact of public institutional quality on economic growth in EU countries for the period of 2002-2019 was investigated. The institutional quality series used in the study; It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…For Asian countries, Goh, Ranjanee, And and Leong (2020) used the non-linear ARDL to show that an asymmetric effect of FDI inflows on economic growth exists. A study involving the European Union (EU) countries by Saritaş and Özmen (2021) showed that the higher the institutional quality, the higher the growth of the economy. In a study for Cote d'Ivoire, Kouadio and Gakpa (2021) used the dynamic ordinary least squares (DOLS) and the fully modified ordinary least squares (FMOLS) to reveal that financial openness had a positive impact on total factor productivity.…”
Section: Empirical Literaturementioning
confidence: 99%
“…For Asian countries, Goh, Ranjanee, And and Leong (2020) used the non-linear ARDL to show that an asymmetric effect of FDI inflows on economic growth exists. A study involving the European Union (EU) countries by Saritaş and Özmen (2021) showed that the higher the institutional quality, the higher the growth of the economy. In a study for Cote d'Ivoire, Kouadio and Gakpa (2021) used the dynamic ordinary least squares (DOLS) and the fully modified ordinary least squares (FMOLS) to reveal that financial openness had a positive impact on total factor productivity.…”
Section: Empirical Literaturementioning
confidence: 99%